Analisis Penggunaan Insektisida Malation dan Temefos Terhadap Vektor Demam Berdarah Dengue Aedes aegypti di Kota Kendari Sulawesi Tenggara - Mubarak Mubarak; Tri Baskoro Tunggul Satoto; Sitti Rahmah Umniyati (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2015)
Malathion and temephos insecticides have long been used at Kendari Municipality in the program of Ae.aegypti mosquito as vector of DHF; however, DHF cases are still relatively high. At Kendari Municipality there is  no  report on  susceptibility status of  Ae.  aegypti larva and  mosquito against malathion and  temephos insecticides. This study aimed to identify association between frequency and duration of malation and temephos usage with the susceptibility status of Ae. aegypti larva and mosquito at Kendari Municipality and to identify resistance mechanism of Ae. aegypti larva and mosquito.  This study was an observational analytic and subjects of the study were Ae. aegypti larva and mosquito collected from five county in Kendari. Susceptibility status of Ae. aegypti larva and mosquito against malathion and temephos was qualitatively assessed through biochemical test and quantitatively assessed through bioassay test. The statistical analysis perform by using Pearson and One Way Anova. as result, biochemical test of Ae. aegypti larva at counties of Kadia, Rahandouna, Kasilampe and Labibia had tolerant status with average score 2.49; 2.15; 2.05; 2.50 and at Abeli had  susceptible status with average score 1.77. Biochemical test of test larva from  Kadia, Rahandouna, Kasilampe, Labibia and Abeli showed susceptibility status  0%, 3.33%, 23.33%, 0% and 16.67% subsequently. The result of bioassay test of Ae. aegypti larva against temephos at Kasilampe was resistant (73.3%), at Rahandouna was tolerant (89.3%) and Kadia, Labibia and Abeli were susceptible (100%). The result of bioassay test of susceptibility status of Ae. aegypti mosquito against malathion was 100% for all counties. In conclusion, frequency and duration of use of malathion and temephos through biochemical test not affected significantly against downgrading susceptibility status of Ae. aegypti larva; whereas through bioassay test there was significant effect. Increase of non specific esterase enzyme in Ae. aegypti larva using biochemical test was not because temephos and malathion usage but because there were other unknown factors.Keywords: Aedes aegypti, temephos, malathion, bioassay test, biochemical test, insecticides.